DETERMINATION OF FUNGAL PATHOGENS ASSOCIATED WITH THE SPOILAGE OF Citrus sinensis (sweet orange) IN GOMBE MAIN MARKET GOMBE STATE, NIGERIA. - ABUBAKAR, B.; KABIRU, M.; NAZEEF, S; ZAINAB, A. (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2023)
Isolation and identification of fungal pathogens associated with the spoilage of citrus sinensis was carried out between September to December 2022 in Gombe main market. Total of thirty samples collected for the analyses. Potato dextrose Agar (PDA) was used for isolation of fungi from the spoilt Citrus sinensis fruits and for the preparation of pure cultures. The isolates pathogenicity was also carried from the pure cultures. Four fungal pathogens were which includes Aspergillus Niger with high frequency number of 47.6%, Aspergillus fumigatus with 29.5% frequency followed by Aspergillus flavus with 14.2% and lastly Rhizopus stolonifer with the lowest frequency of 9.5%. The isolates were identified by comparing their characteristics with those of known taxa and also based on macro-morphological and micro-morphological characteristics.